(untitled) (Indonesian Economic Justice Review, 2024)
This paper examines the legal and policy challenges that Indonesia’s rural poor face in securing access to land and natural resources, which are essential for economic empowerment and social justice. Land is a key resource for rural populations, particularly for small-scale farmers and indigenous communities, but access to land remains highly unequal due to historical land dispossession, unclear land tenure laws, and encroachment by large corporations. The paper investigates the impact of land-related legal frameworks, such as the 1960 Basic Agrarian Law, on the rural poor, focusing on issues of land rights, land grabbing, and the allocation of state land for large-scale agricultural projects. Through a combination of legal analysis, field studies, and interviews with affected communities, the paper highlights the difficulties faced by rural populations in asserting their land rights and the often exploitative practices that occur in land negotiations. The paper also examines government policies aimed at promoting land redistribution, such as the 2012 Agrarian Reform Program, and assesses their effectiveness in addressing land inequality. The findings suggest that despite policy efforts, many rural communities remain landless or subject to insecure land tenure, which perpetuates poverty and inequality. The paper concludes by proposing legal reforms to improve land access for the rural poor, including clearer land tenure systems, better land dispute resolution mechanisms, and stronger protections against land grabbing.